Assesing the role of work motivation on employee performance - Nurul Athirah, Zaaba (2014)
This study was aimed to examine the perception of teachers in a school located in Port Klang, Selangor, Malaysia about the role of work motivation on employee performance. The independent variables used in this study are extrinsic motivation and intrinsic motivation. For the dependent variable is the employee performance. This study was conducted to identify the factors that motivate employee as well as to identify the role of work motivation towards employee performance. A Statistical Package for the Social Sciences (SPSS) was used to analyse the data. Correlation analysis showed that there was a significant correlation between work motivation and employee performance. Regression analysis showed that the factors of work motivation consists of professional development/conference, job promotion, money as well as education/classes or seminars which contribute directly towards employee performance. The significant of this study besides able to identify the factors, it is also to create awareness for the organization to have fully understanding on work motivation of the employees since it might have great impact to the organization